(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The present article reveals the main problems of parenting a child with developmental disabilities. It is known, that the upbringing, education and development of a child starts in the family. However, the solution of these essential tasks is significantly complicated in a family raising a child with various developmental disabilities. The success of this study depends on how well parents are informed about the psychophysical characteristics of the child’s development; about using the means, methods and conditions for organizing and conducting therapeutic, recreational and core-developmental activities in a family. This defines the necessity to study the problem of a family raising a child with developmental disabilities. In the general system of upbringing and educating a child with special needs, the role of the family and the awareness of parents in these matters is immeasurably increasing. The special scientific and methodological literature emphasizes the importance of studying the problem of parenting a child with developmental disabilities, providing informational assistance to parents in raising those children in a family environment. However, insufficient knowledge of the problem of a family raising a child with developmental disabilities significantly complicates the effective solution of many issues of this problem. The foregoing defines the relevance of this study, its theoretical and practical significance.